The Role of Islamic Banking in the Indonesian Economy - Wulandari, Putri (Economic and Business Horizon, 2024)
Islamic banking has played a strategic role in driving Indonesia's economic growth through the application of Islamic financial principles oriented toward justice, transparency, and inclusiveness. Unlike the conventional banking system, Islamic banking avoids practices such as riba (usury), maysir (speculation), and gharar (uncertainty), and implements Sharia-compliant contracts such as profit-sharing (mudharabah, musyarakah) and sales-based contracts (murabahah). Beyond its function as a financial intermediary, Islamic banking also actively manages social funds such as zakat, infaq, and shadaqah, which are distributed to improve the welfare of underprivileged communities. Furthermore, its contribution to the Micro, Small, and Medium Enterprises (MSME) sector through productive financing helps create jobs and strengthens the national economy's competitiveness. Thus, Islamic banking serves as a vital instrument in realizing an inclusive, sustainable, and just economy.